Perilaku Politik Masyarakat dalam Memilih Presiden dan Wakil Presiden pada Pemilu 2024 (Studi di Desa Winong Kecamatan Gempol Kab. Pasuruan) - Alfarisi, M. Salman (Jurnal Ilmiah Widya Sosiopolitika, 2025)
Public political participation in elections is a crucial indicator of democracy. This study aims to examine the political behavior of citizens in choosing the President and Vice President during the 2024 General Election, and to identify the factors influencing voting decisions in Winong Village, Gempol Sub-district, Pasuruan Regency. The research uses a descriptive qualitative method with data collected through interviews, observations, and literature review. The findings reveal four voter typologies in the village: critical, rational, skeptical, and traditional voters, with rational and traditional voters being the dominant groups. The factors influencing voting behavior are divided into two categories: internal factors, such as political awareness and social influence, and external factors, such as candidate image, policy issues, party affiliation, and media exposure. These findings highlight the importance of local context and the media’s role in shaping political behavior at the village level.